The development and architectural significance of early Etrusco-Italic podia - Potts, C (Peeters Online Journals, 2011)
The incorporation of podia into Etruscan and Latial religious buildings during the 6th century BC marks the emergence of temples as a distinct architectural form in both the urban landscape and the archaeological record. Consideration of the significance of this change in elevation, however, has largely been overlooked to date in preference for the presentation of podia as a Roman form derived from Etruscan sacred aesthetics. This review of the evidence for the chronological and geographical development of podia in central Italy will suggest a means of differentiating podia from other substructures, demonstrate that they can be recognised in Latium before Etruria, and argue that their introduction may represent an architectural response to particular local conditions.